(untitled) (SigMe, 2024)
Syphilis, a growing concern in Argentina, has markedly risen in recent years. This analytical and quantitative study aimed at analysing syphilis cases in patients aged 15-65 years between 2021 and September 2023 at San Javier Hospital, Santa Fe. An increase in cases was noted, especially among young people aged 15 to 24 years, who accounted for 56% of positive diagnoses, demonstrating a clear relationship between age and case confirmation. High positivity rates were observed in women, including pregnant women. The Venereal Disease Research Laboratory (VDRL) was the most commonly used test, and many patients were uninsured. These findings highlight the need for preventive measures, comprehensive sexuality education programmes, access to the healthcare system and early detection in at-risk groups, particularly in young people and pregnant women.